Association between added sugar intake and mortality is nonlinear and dependent on sugar source in 2 Swedish population–based prospective cohorts. Issue 2 (26th December 2018) - Ramne, Stina; Alves Dias, Joana; González-Padilla, Esther; Olsson, Kjell; Lindahl, Bernt; Engström, Gunnar; Ericson, Ulrika; Johansson, Ingegerd; Sonestedt, Emily
ABSTRACT: Background: Although sugar consumption has been associated with several risk factors for cardiometabolic diseases, evidence for harmful long-term effects is lacking. In addition, most studies have focused on sugar-sweetened beverages (SSBs), not sugar per se. Objective: The aim of this study was to examine the associations between added and free sugar intake, intake of different sugar sources, and mortality risk. Methods: Two prospective population-based cohorts were examined: the Malmö Diet and Cancer Study (MDCS; n  = 24, 272), which collected dietary data by combining a food diary, interview, and food-frequency questionnaire (FFQ), and the Northern Swedish Health and Disease Study (NSHDS; n  = 24, 475), which assessed diet with an FFQ. Sugar intakes defined as both added and free sugar and different sugar sources were examined. The associations with mortality were examined using a multivariable Cox proportional hazards regression. Results: Higher sugar consumption was associated with a less favorable lifestyle in general. The lowest mortality risk was found with added sugar intakes between 7.5% and 10% of energy (E%) intake in both cohorts. Intakes >20E% were associated with a 30% increased mortality risk, but increased risks were also found at intakes <5E% [23% in the MDCS and 9% (nonsignificant) in the NSHDS]. Similar U-shaped associations were found for both cardiovascular and cancer mortality in the MDCS. By separately analyzing the different sugar sources, the intake of SSBs was positively associated with mortality, whereas the intake of treats was inversely associated. Conclusions: Our findings indicate that a high sugar intake is associated with an increased mortality risk. However, the risk is also increased among low sugar consumers, although they have a more favorable lifestyle in general. In addition, the associations are dependent on the type of sugar source.